Associations Between Sleep Quality, Mental Health, and Vitality in Professional Drivers: A Cross-Sectional Study - Gabriela Roxana Louisse Neacşu; Agripina Rașcu (Clocks & Sleep, 2026)
Professional drivers are exposed to work conditions that may affect sleep quality. Although poor sleep quality has been associated with lower mental health (MH) and vitality (VT), its relationship with these outcomes in professional drivers remains unclear. This cross-sectional study examined the association between sleep quality and selected health-related quality-of-life (HRQoL) domains among 399 professional drivers. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). At the same time, HRQoL was evaluated using the Mental Health, Vitality, and Bodily Pain domains of the 36-Item Short Form Health Survey. Correlation and regression analyses were performed. The mean PSQI score was 8.59, indicating overall poor sleep quality. Higher PSQI scores were negatively associated with MH (ρ = −0.384, p < 0.001) and VT (ρ = −0.495, p < 0.001). Sleep quality remained an independent predictor of MH (B = −2.47, p < 0.001; R2 = 0.155) and VT (B = −4.10, p < 0.001; R2 = 0.268), whereas age showed a modest association only with VT (B = −0.235, p = 0.035). Poor sleep quality was associated with lower MH and VT scores among professional drivers. The stronger association observed for VT suggests that sleep quality may be particularly relevant to energy levels and daily functioning in this study population.